PENINGKATAN KEMAMPUAN KONEKSI MATEMATIS DAN SELF EFFICACY SISWA DALAM PEMBELAJARAN GEOMETRI MENURUT TEORI VAN HIELE DENGAN PENDEKATAN BUDAYA SUNDA DI SEKOLAH MENGAH ATAS - Pujia Siti Balkist (UJMES (Uninus Journal of Mathematics Education and Science), 2018)
The purpose of this research is (1) to know the improvement of mathematical connection ability in the students who get thegeometry learning according to Van Hiele theory with the Sundanese culture approach compared with the students who getthe conventional learning. (2) to know the improvement of self efficacy in the students who get the geometry learning accordingto Van Hiele theory with the Sundanese cultural approach compared to the students who get the conventional learning. (3)to know the relationship between the ability of mathematical connection with self efficacy in the learning of geometry. Thisresearch is a quasi experimental design experiment using non-equivalent control group pretest-posttest design. The subjectsof this study are the students of grade XI SMAN 1 Sukabumi and SMAN 3 Sukabumi academic year 2014/2015.The variable of this research consists of 2 variables, namely independent variables in the form of learning geometry accordingto van hiele theory with the approach of Sundanese culture and dependent variable in the form of mathematical connectionability and student self efficacy. Technique of collecting research data using mathematical connection ability test on geometrymaterial and self efficacy scale. Technical analysis of data in this study using inferential statistics which includes t-test sampleindependent and Pearson product moment correlation analysis. This test is done with the help of SPSS Version 20.00software. The results showed that the improvement of mathematical connection ability of students who acquired geometrylearning according to Van Hiele theory with the Sundanese culture approach differed significantly compared to students whoreceived conventional learning and increased self efficacy of students who acquired geometry learning according to Van Hieletheory with different Sundanese cultural approach significantly compared with students who received conventional learning,but there is no significant relationship between mathematical connection ability and self efficacy of students on learninggeometry.